2021
DOI: 10.12659/msm.930215
|View full text |Cite
|
Sign up to set email alerts
|

H Long Terminal Repeat-Associating 2 (HHLA2) is a Biomarker of Advanced Stage Hepatocellular Carcinoma and Promotes Tumor Cell Development In Vitro

Abstract: Background Several risk factors contribute to the inflammation promoting hepatocellular carcinoma (HCC) development, but the underlying mechanisms are unknown. Human endogenous retrovirus H long terminal repeat-associating 2 (HHLA2), a B7 family member, is highly expressed in various malignant tumor tissues and is related to tumor progression and metastasis. Material/Methods Bioinformatics analysis was used to analyze the gene expression chip GSE33006 of HCC tissue in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
(19 reference statements)
3
16
0
Order By: Relevance
“…This is consistent with another study that over-expression of HHLA2 is a protective factor for KIRC (kidney renal clear cell carcinoma) patients [22]. In Luo's study, HHLA2 was also reported to be overexpressed in HCC, compared with normal liver tissue, the expression of HHLA2 was associated with poor prognosis of HCC patients [23,24]. But in another HCC study, Liao et al indicated that HHLA2 is frequently expressed in HCC, and positive HHLA2 correlates with higher CD8 + cell density and favorable prognosis [25].…”
Section: Introductionsupporting
confidence: 88%
“…This is consistent with another study that over-expression of HHLA2 is a protective factor for KIRC (kidney renal clear cell carcinoma) patients [22]. In Luo's study, HHLA2 was also reported to be overexpressed in HCC, compared with normal liver tissue, the expression of HHLA2 was associated with poor prognosis of HCC patients [23,24]. But in another HCC study, Liao et al indicated that HHLA2 is frequently expressed in HCC, and positive HHLA2 correlates with higher CD8 + cell density and favorable prognosis [25].…”
Section: Introductionsupporting
confidence: 88%
“…36–38 In our previously published work, we found that HHLA2 was highly expressed in HCC tissues, and was correlated with development and progression in HepG2 cells. 39 We used the LinkOmics online database to analyze pathways in HCC that potentially involve HHLA2. We identified three genes closely related to HHLA2: TFF2, FABP6, and PPP1R14D.…”
Section: Discussionmentioning
confidence: 99%
“…A similar upregulation of HHLA2 was observed in hepatocellular carcinoma, and the knockdown of HHLA2 increased cell adhesion, accelerated cell apoptosis, resulted in cell arrest and suppressed cellular processes. 22 The overexpression of HHLA2 inhibited cell proliferation of ovarian cancer. 19 The observed promoted effect of HHLA2 on PTC cells provides a view that the inhibition of HHLA2 might be a novel therapeutic strategy of PTC treatment.…”
Section: Discussionmentioning
confidence: 99%